The role of environmental attitude towards ecological behavior of early adulthood in Jakarta greater area (Jabodetabek) - Ade Iva Murty; Andita Putri Ramadhania; Alfin Adichandra; Dienia Airlia (Jurnal Ecopsy, 2022)
Ecological behavior is the most important factor to slow down climate change. This research aims to investigate the role of Environmental Attitude towards Ecological Behavior. This research utilized the mixed-method approach and consisted of 191 respondents and 2 pro-environmental groups. Quantitative data was collected through an online survey and qualitative data was collected through interviews. A simple regression model test showed that Environmental Attitude positively and significantly affects ecological behavior. After controlling for demographic factors such as gender, residency, source of income, and education level. It was found that these variables do not have significant effects on ecological behavior. Meanwhile, case studies reflect themes such as values of environment, technological use, the role of young volunteers, and past experiences. So, it can be concluded that the early adults in Jabodetabek implements ecological behavior as an effect of Environmental Attitude, and as a lifestyle. Most of respondents tend to use social media as a way of expressing their opinions and ideas regarding environmental problems. Therefore, if the government or other organizations have some programs for increasing the awareness of early adult in Jabodetabek to implement ecological behavior practice, they should focus on developing social media campaigns that will improve early adult environmental attitudes.